Aspek Hukum Perlindungan Konsumen E-Commerce - Sunusi, Masri (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2013)
E-Commerce is the buying and selling is done through the internet, which can be beneficial to consumers, but on the other hand sometimes harm consumers, because they often do not get the protection that gives a certainty in the event of a dispute.In the E-commerce business transactions which are characteristic of business to business transactions where businesses that conduct transactions with fellow entrepreneurs, business-to- consumer transactions while the transaction is carried out by the NII businesses with consumers themselves.The  benefits  of  E-Commerce  transactions  for  consumers,  the consumer can conduct transactions for 24 hours without leaving the house and did not require transport to the cost of sales. Protection to consumer E-Commerce is basically set in two forms namely, first, by the laws of a general nature, and secondly, the agreement is specific and has its own characteristics which is made by both parties, ie between businesses and consumers.